Alcohol use and depression: link with adherence and viral suppression in adult patients on antiretroviral therapy in rural Lesotho, Southern Africa: a cross-sectional study. (December 2016) - Cerutti, Bernard; Broers, Barbara; Masetsibi, Motlomelo; Faturiyele, Olatunbosun; Toti-Mokoteli, Likabelo; Motlatsi, Mokete; Bader, Joelle; Klimkait, Thomas; Labhardt, Niklaus
Abstract Background Depression and alcohol use disorder have been shown to be associated with poor adherence to antiretroviral therapy (ART). Studies examining their association with viral suppression in rural Africa are, however, scarce. Methods This study reports prevalence of depressive symptoms and alcohol use disorder, and their potential association with adherence and viral suppression in adult patients on ART in ten clinics in rural Lesotho, Southern Africa. Results Among 1, 388 adult patients (69 % women), 80.7 % were alcohol abstinent, 6.3 % were hazardous drinkers (men: 10.7 %, women: 4.4 %, p < 0.001). The prevalence of depressive symptoms was 28.8 % (men 20.2 %, women 32.7 %, p < 0.001). Both alcohol consumption (adjusted odds-ratio: 2.09, 95 % CI: 1.58-2.77) and alcohol use disorder (2.73, 95 % CI: 1.68-4.42) were significantly associated with poor adherence. There was, however, no significant association with viral suppression. Conclusions Whereas the results of this study confirm previously reported association of alcohol use disorder with adherence to ART, there was no association with viral suppression. Trial registration April 28th 2014;NCT02126696 .